First report of Serratia marcescens associated with black rot of Citrus sinensis fruit, and evaluation of its biological control measures in Bangladesh [version 1; peer review: 1 approved, 2 approved with reservations] - Mohammed Faruk Hasan (F1000 Research Ltd, 2020)
Background: The present study was designed to isolate and identify the phyto-pathogen responsible for black rot of Citrus sinensis, and to determine its biological control measures. Methods: The pathogen was isolated from infected oranges and cultured on Luria-Bertani medium. Gram staining method was used to identify the morphological characteristics of the causal agents of the black rot. Advanced molecular technique was applied to facilitate proper detection of the isolated bacteria. Phylogenetic trees were analyzed using the Neighbor-Joining method. Antimicrobial screening was conducted by disc diffusion method. Antagonistic activity was evaluated by well diffusion method. Results: Gram staining of the causal agent showed rod shaped, small and pink bacteria. Polymerase chain reaction of the 16S ribosomal RNA gene amplified an approximately 1465 bp product. The nucleotide sequences of the isolated bacterial sample 1 (BS1) and bacterial sample 2 (BS2) had 99.34% and 99.45% similarities with the reference of Serratia marcescens sequence in NCBI GenBank. The obtained sequences were deposited in GenBank. Two isolates showed virulence capability on some fresh fruits, which confirmed the stain detection and Koch’s postulates. Allium sativum extract showed the largest (27.33±1.5 mm) diameter of zone of inhibition against BS1, at 30µg/disc concentration. In the antagonistic assay, Rhizobium leguminosarum showed largest (19±1 mm) zone of inhibition against BS1. Conclusions: Findings of the current investigations are constructive for identification of causative pathogens in Citrus sinensis black rot disease and their biological control measures.